The three-dimensional composite analysis method of mesoscale eddies in the Philippine Sea based on sound speed profile clustering - Zhou, Xingyu; Li, Qinghong; Yu, Xiangjun; Zhang, Gengming; Ma, Yaowei (Frontiers in Marine Science, 2025)
Traditional composite methods for mesoscale eddies predominantly employ simplistic geographical partitioning, seldom taking into account the variations in mesoscale eddy structures that are jointly influenced by seasonal and regional factors within the area., nor does it consider the issue of approximating mesoscale eddies as elliptical structures. This study combines mesoscale eddy data from satellite altimetry (2007-2022) with Argo profile data captured by eddies to propose a mesoscale eddy composite analysis method based on profile clustering and an elliptical model. This method provides the three-dimensional structures of various types of mesoscale eddies in the Philippine Sea. The results show that the eccentricity of the best-fitting ellipses for mesoscale eddies in the Philippine Sea is predominantly between 0.7 and 0.9, with the orientation of the major axis mostly directed at 80° northeast. Based on sound speed profile clustering, mesoscale eddies are classified into five categories. The composite eddy anomaly structures exhibit a clear correlation with the profile types. Compared to the single mesoscale eddy structure obtained by the traditional mesoscale eddy composite method, this approach accurately composites five typical mesoscale eddy structures in the Philippine Sea, and its elliptical shape is more consistent with actual observational results.